Dampak Pembangunan Wisata Hutan Mangrove Di Pasir Panjang, kecamatan Mempawah Hilir, Kabupaten Mempawah - Richard Septhrus Riyanto; Sawitri O E (Tanjungpura University, 2020)
The purpose of this research is to study, titled Impact of tourism development in the village of Sand Mangrove Park, District Mempawah Hilir Regency Mempawah. With the problem of how the form of livelihoods, theeconomic condition of the community after the development, and social relations that exist around mangrove forest tourism. This research method is a qualitative research approach. This type of research is a case study. The words and actions of the person being interviewed or observed are the main data sources. The main data sources are recorded through written records or through video / audio tapes recording, taking photos or films. Data collection techniques used were interviews, observation, and study of documentation. Analysis of the data used is data reduction, data presentation, and drawing conclusions. The results showed that: The impact of social change in terms of livelihoods and economic conditions is very beneficial to the community because of the development of the mangrove park tourism can increase people's income and livelihood of the community also increased where the livelihood of the community initially farmers or fishermen can also workas parking attendants, traders or crossing services and in terms of social relations also the community in the area is very good.